An open source automatic feeder for animal experiments. (April 2017) - Oh, Jinook; Hofer, Riccardo; Fitch, W. Tecumseh
Abstract: Automatic feeders are widely used in animal experiments to dispense an accurate amount of food reward for each trial. Several commercial automatic feeders for animal experiments are available which are specific to certain species and food types. However, it would be beneficial for researchers if they could easily build their own experimental feeders customized for their study species, food types, and other experimental considerations. In this paper, we describe an open source experimental feeder using an Arduino microcontroller. The design of the feeder is focused on simplicity to provide a straight-forward building process and allow custom modifications for various requirements. The cost for building this feeder is less than €200 and we have successfully tested our design with three different food types for pigeons, cats, and marmoset monkeys.